Efficacy and Tolerability of Pharmacotherapies to Aid Smoking Cessation in Adolescents - Bailey, Steffani R. (2012)
Adolescent smoking remains a public health problem. Despite concerns regarding adolescent nicotine dependence, few well-designed smoking cessation studies have been conducted with teen smokers. This is particularly true regarding pharmacological treatments for nicotine dependence. Currently, pharmacological aids are not recommended for treating adolescent nicotine dependence, as efficacy has not been shown in this population. This review includes studies that have examined the efficacy of pharmacotherapy for smoking abstinence and/or reduction in cigarette consumption among adolescent smokers who want to quit smoking, lab-based adolescent studies that have examined the effectiveness of these medications in reducing cravings and/or withdrawal symptoms, and/or studies that have assessed the tolerability of medications for smoking cessation in adolescent smokers. This review provides information on the pharmacologic action of each medication, the efficacy of each medication for adolescent smoking cessation, the tolerability of each medication based on reported adverse events, and compliance with the medication protocols. Thirteen relevant articles were identified and included in the review. Nicotine patch, nicotine gum, nicotine nasal spray, bupropion, and varenicline have been studied in adolescent smokers. The adverse events reported in the studies on pharmacology for adolescent smoking suggest that the side effect profiles for nicotine replacement therapy, bupropion, and varenicline are similar to those reported in adult studies. There is some evidence of efficacy of nicotine patch and bupropion at end of treatment (efficacy of varenicline has not been assessed), but none of the medications included in this review were efficacious in promoting long-term smoking cessation among adolescent smokers. It is noted that many of the study protocols did not follow the recommended dose or length of pharmacotherapy for adults, rendering it difficult to determine the true efficacy of medication for adolescent smoking cessation. Future efficacy studies are warranted before recommending pharmacotherapy for adolescent smoking cessation.